Design and test of a pulse-width modulator and driver for space-borne GaN switch mode power amplifiers in P-band. Issue 3 (4th March 2015) - Ghosh, I. S.; Altmann, U.; Cabria, L.; Cipriani, E.; Colantonio, P.; Ayllon, N.; Chowdhary, A.; Kersten, O.; Quibeldey, M.; Follmann, R.
Abstract : In this paper, the design and test of a single-chip RF pulse-width modulator and driver (PWMD) aimed at exciting a high-power class-E GaN high-power stage at 435 MHz is described. For the required buffer size, avoiding potential ringing of the pulses within the buffer structure presents a major challenge in the design process. Therefore, a smaller test chip capable of driving capacitive loads of up to 5 pF was initially designed, fabricated, and tested. An approach based on three-dimensional electromagnetic simulations was used to validate the test results and offers excellent simulation accuracy. Based on the results obtained for test chip an enlarged PWMD chip capable of driving a 40 W high-power stage has been designed and tested on passive loads representing the targeted final stage.